2021
DOI: 10.1080/13632752.2021.1894743
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review exploring the views and experiences of children and young people of the label Social, Emotional and Mental Health (SEMH)

Abstract: A systematic literature review exploring the views and experiences of children and young people of the label Social, Emotional and Mental Health (SEMH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As illustrated in the current study, these stigmas are influenced by several factors, including differences in a person's group membership, social contacts, exposure to literacy campaigns, and education levels (Committee on the Science of Changing Behavioural Health Social Norms et al, 2016;Stuart, 2016). 'Labels' such as emotional and behavioural difficulties, may also perpetuate negative perceptions about students with social, emotional, and behavioural difficulties (Hickinbotham and Soni, 2021). However, previous studies suggested that the impact of such labelling is more complex for the students.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As illustrated in the current study, these stigmas are influenced by several factors, including differences in a person's group membership, social contacts, exposure to literacy campaigns, and education levels (Committee on the Science of Changing Behavioural Health Social Norms et al, 2016;Stuart, 2016). 'Labels' such as emotional and behavioural difficulties, may also perpetuate negative perceptions about students with social, emotional, and behavioural difficulties (Hickinbotham and Soni, 2021). However, previous studies suggested that the impact of such labelling is more complex for the students.…”
Section: Discussionmentioning
confidence: 80%
“…However, previous studies suggested that the impact of such labelling is more complex for the students. While the labels may represent stigmas and negative expectations (Lauchlan and Boyle, 2007;Mowat, 2015), they can also help students understand their individual needs and fulfil their need for belongingness and autonomy (Cosma and Soni, 2019;Hickinbotham and Soni, 2021). To reduce stigmas, good role models and adequate knowledge of disorders may be helpful (Tanaka et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the evidence base is compelling for using student data to guide instructional decisions (Jung et al, 2018) and seeking perspectives from students themselves is a vital component (Hickinbotham & Soni, 2021;Horgan et al, 2023). Lower competence in this subscale suggests the need for dedicated training on becoming a critical reflective practitioner to help teachers effectively gain evidence from the range of sources available to them, including the student themselves, and evaluate that knowledge to inform their practice.…”
Section: Examining Inclusive Education Practices Using the Srfmentioning
confidence: 99%
“…I interpreted that for all participants, talking about mental health triggered thoughts, feelings and associations related to their own personal experiences, which shapes their own stories and consequently, steered their discussions in different directions. (Hickinbotham & Soni, 2021). Here, it is useful to draw on previously explored ideas by Tuffin et al (2001) who discussed how language around mental health shapes understanding.…”
Section: 1: Research Question 1 Andmentioning
confidence: 99%
“…EPs must recognise the key role they play in supporting teachers to interpret mental health discourses and make sense of the teacher role in children's mental health (Monkman, 2013). Teachers may benefit from regular opportunities to discuss the use of mental health language and labels to reflect on classroom implications (for example, how this affects perceptions of the child and understanding of appropriate support) (Hickinbotham & Soni, 2021). This should form part of whole-school considerations and policies and the use of mental health discourse (Dimitrellou & Hurry, 2018).…”
Section: 4: Recommendations For Practicementioning
confidence: 99%